Management of Pulse Generators in a Breast Cancer Patient with in Situ Subthalamic Nucleus Deep Brain Stimulation - Son, Byung-chul; Kim, Joong-Seok; Park, Woo-Chan; Ko, Hak-cheol (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Although deep brain stimulation (DBS) has been used for > 25 years in the treatment of movement disorders, no report has been published on the management of DBS pulse generators implanted in the anterior chest in patients with breast cancer who require mastectomy, radiotherapy, and future imaging studies.We describe a 62-year-old female patient with advanced Parkinson's disease (PD) who was dependent on bilateral subthalamic nucleus (STN) DBS. She was diagnosed with cancer in her left breast. To avoid difficulties in imaging studies, surgery, and radiotherapy related to the breast cancer, bilateral pulse generators for STN DBS previously implanted in the anterior chest wall were repositioned to the anterior abdominal wall with replacement of long extension cables. During mastectomy and the relocation of the pulse generators, we were not aware of the risks of an open circuit and neuroleptic malignant-like syndrome due to our limited knowledge about how to manage DBS hardware.Coincident breast cancer and the need for STN DBS is underreported. Considering the uncertainties in the management of pulse generators and the incidence of breast cancer, guidelines for handling DBS hardware in the setting of cancer are needed. More careful attention should be paid to performing magnetic resonance imaging in DBS-dependent patients with chronic PD.
Keywords: breast cancer; deep brain stimulation; Parkinson's disease; pulse generator; radiotherapy